2007
DOI: 10.1016/j.febslet.2007.02.046
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of membrane topology of neutral sphingomyelinase 2

Abstract: Neutral sphingomyelinase 2 (nSMase2), which has two hydrophobic segments at its NH 2 -terminus, plays an important role in ceramide-mediated cell regulation. Here, we investigated the membrane topology of nSMase2. When a double-tagged nSMase2 at both the NH 2 and COOH termini, was overexpressed in MCF-7 cells, the signals from both tags were detected in the inner leaflet of the plasma membrane. Furthermore, insertion of a tag into the internal sequence and green fluorescent protein-fused deletion mutants revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 21 publications
4
50
0
Order By: Relevance
“…N-SMase was virtually undetectable on the cell exterior (0.4% of total immunoreactivity; Figure 5A). Combined with the confocal images, these findings indicate that the great preponderance of N-SMase activity is associated with the cytofacial leaflet of the plasma membrane, as described previously (23) this effect precludes the possibility of N-SMase neosynthesis, suggesting instead that FMLP induces changes in the conformation or microenvironment of N-SMase that enhance the intensity of its immunolabeling. In keeping with this observation, previous work demonstrated that FMLP stimulation doubles the N-SMase activity associated with plasma membrane fractions in vitro (16).…”
Section: Immunolocalization Of N-smasementioning
confidence: 53%
“…N-SMase was virtually undetectable on the cell exterior (0.4% of total immunoreactivity; Figure 5A). Combined with the confocal images, these findings indicate that the great preponderance of N-SMase activity is associated with the cytofacial leaflet of the plasma membrane, as described previously (23) this effect precludes the possibility of N-SMase neosynthesis, suggesting instead that FMLP induces changes in the conformation or microenvironment of N-SMase that enhance the intensity of its immunolabeling. In keeping with this observation, previous work demonstrated that FMLP stimulation doubles the N-SMase activity associated with plasma membrane fractions in vitro (16).…”
Section: Immunolocalization Of N-smasementioning
confidence: 53%
“…It has been reported that PC in the cytoplasmic side of the plasma membrane is hydrolysed by PC-specific phospholipase C (Ramoni et al, 2004) and phospholipase D2 (PLD2) (Du et al, 2004). Sphingomyelin is also digested by intracellular neutral sphingomyelinase 2 (Tani and Hannun, 2007). In both cases, signalling lipids, including diacylglycerol, PA, ceramide and sphingosine-1-phosphate (Nagata et al, 2006) are formed.…”
Section: Discussionmentioning
confidence: 99%
“…3), with weak Runx2 binding to the -562 to -557 region despite the strong transactivating power of this region. smpd3 appears to play a role in the mineralization of bone and dentine (20).…”
Section: Discussionmentioning
confidence: 99%